Garcinia atroviridis (Botani, Pemanfaatan dan Bioaktivitasnya) - Marina Silalahi (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
Garcinia atroviridis is a species in the Clusiaceae family that has long been used by humans as a spice and traditional medicine. The use of G. atroviridis as a spice and traditional medicine is related to its secondary metabolites and bioactivity. The method of writing this article is a review of the literature published online, especially on Google scholars, using the keyword Garcinia atroviridis, uses of G. atroviridis and bioactivity of G. atroviridis. The articles or research results obtained were reviewed and then synthesized so that comprehensive information was obtained about the botany, benefits and biactivity of G. atroviridis. Garcinia atroviridis can be identified by the thin, pale yellow sap produced on the stems. Ethnobotany G. atroviridis is used for cooking spices to enhance taste, produce a sour / fresh taste and increase food resistance. Bioactivity of G. atroviridis is anti-obesity, anti-microbial, antioxidant and anti-cancer. Garcinia atroviridis contains hydroxycitric acid (HCA, or (-) - HCA) which is associated with bioactivity as an anti-obesity because it inhibits ATP-citrate lyase. Bioactivity as an antimicrobial can be developed into a natural food preservative.